2020
DOI: 10.1093/jrs/feaa043
|View full text |Cite
|
Sign up to set email alerts
|

Linking Migration Aspirations to Integration Prospects: The Experience of Syrian Refugees in Sweden

Abstract: In this article, we examine the shifting role of aspirations in migration and integration processes by focusing on the experiences of a group of Syrian refugees settling in Sweden. We demonstrate that aspirations and capabilities may be used to study the lives of refugees (and immigrants) before, during, and after migration and that through a sequential study of aspirations it is possible to determine how refugees come to envision possible life trajectories in destination countries. Understanding the relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…As previous research has shown, refugees' aspirations and motivations are important to study as they significantly influence their choices and actions and thus, their incorporation trajectory (Borselli and Meijl, 2020;Meeteren, 2014). Although a growing body of research has started to explore refugees' aspirations (Borselli and van Meijl, 2020;van Heelsum, 2017;Müller-Funk, 2019), few have examined them over time. In particular, few have examined refugees' aspirations over the course of the asylum-seeking and the subsequent resettlement process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous research has shown, refugees' aspirations and motivations are important to study as they significantly influence their choices and actions and thus, their incorporation trajectory (Borselli and Meijl, 2020;Meeteren, 2014). Although a growing body of research has started to explore refugees' aspirations (Borselli and van Meijl, 2020;van Heelsum, 2017;Müller-Funk, 2019), few have examined them over time. In particular, few have examined refugees' aspirations over the course of the asylum-seeking and the subsequent resettlement process.…”
Section: Discussionmentioning
confidence: 99%
“…Müller-Funk (2019) focuses on Syrian refugees in Turkey and finds that their aspirations to stay in Turkey were shaped by their hope to return to Syria as well as life satisfaction in Turkey. Borselli and van Meijl (2020) explore the aspirations of Syrian refugees in Sweden and highlight the active role of refugees and their aspirations in shaping migration and integration dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the foundation of integration focuses on the domain of rights and citizenship (Platts-Fowler & Robinson, 2015). A growing number of researchers have called on scholars to conceptualize integration as a multidimensional process in which refugees' inclusive participation in diverse domains is critical for their quality of life and maintaining their new and original culture (Borselli & van Meijl, 2020;Phillimore, 2020;Ward et al, 2020). This article responds to these scholars' call and employs a multidimensional analysis of integration which builds on the understanding that each refugee lives and functions in all domains.…”
Section: Integration Theoriesmentioning
confidence: 99%
“…La migration correspond donc à la recherche d'un avenir meilleur par rapport à un contexte jugé insatisfaisant, associée à l'hypothèse qu'un avenir ailleurs sera plus favorable(Czaika et Vothknecht 2014 ;Boccagni 2017 ;Carling et Schewel 2018). De plus en plus de chercheur•euses s'intéressent aux aspirations des migrant•e•s(Van Meeteren et al 2009 ;Czaika et Vothknecht 2014 ;Boccagni 2017 ;Carling et Schewel 2018 ;Borselli et van Meijl 2020 ;Wang et Collins 2020 ;Vitus 2021). La littérature souligne qu'il est pertinent d'étudier les aspirations même si elles ne se réalisent pas car elles révèlent des éléments essentiels de l'expérience vécue, tels que la manière de donner du sens à sa vie présente ainsi que la perception des contraintes structurelles et de ses propres capacités et ressources…”
unclassified